Symmetric Distributed Joint Source-Channel Coding Using Raptor Codes - Xuqi Zhu; Wenbo Zhang; Bin Li; Lin Zhang (2010 International Conference on Networking Architecture and Storage, 2010)
Distributed compression of correlated sources has been discussed much in wireless sensor networks, while the error-resilient implementation of this efficient coding strategy is one of the crucial issues for applications. In this paper, a symmetric Distributed Joint Source-Channel Coding (DJSCC) scheme is proposed by using Raptor codes for the independent channels case. The channel noise and the correlation of sources are considered simultaneously within one set of encoder and decoder. The symmetric structure of the proposed approach leads to more flexible and balanced rate allocation, and the rateless property of Raptor codes also guarantees tractable code rates and error correction. At last, the simulation results demonstrate that our scheme outperforms the existing LDPC-based scheme at low SNR.